Design and Analysis of Rectangular Microstrip Array Antenna at Ka Band Becon Frequency 20.2GHz - Kohitha Bai, Bondili.; Immadi, Govardhani. (International Journal of Engineering and Technology, 2018)
The design and analysis of single double (1Ã—2) and four (1Ã—4) element linear rectangular micro strip array antennas is done to achieve high gain and directivity. The operating frequency of the proposed array antenna is Ka-band, 20.2GHz which is a Beacon frequency of GSAT-14 launched by ISRO. The substrate material used is common for the single, double (1Ã—2) and four (1Ã—4) i.e. FR4 with a thickness of 0.8mm and the dielectric constant is 4.4. The antenna elements are placed uniform at a same distance. The feeding network used here is a parallel or corporate feed network. The power splitting and impedance matching is done using RF Wilkinson power divider. The entire proposed micro strip phased array antenna is evaluated using HFSS software tool. Â Â